Leptin inhibits AMPKα2 down-regulation induced decrease in the osteocytic MLO-Y4 cell proliferation and the expression of osteogenic markers - Fan, Qing (Int J Clin Exp Pathol, 2017)
AMP-activated protein kinase (AMPK) is of biological and clinical importance for regulating cellular and systemic energy homeostasis. Although AMPKα1, one of the two AMPK’s catalytic subunit α, expresses in the bone and stimulates bone nodule formation, the role of AMPKα2 in osteogenesis remains incompletely understood. The aim of this study was to determine the role of AMPKα2 in osteocytic MLO-Y4 cellproliferation and the expression of osteogenic markers. The current study silenced AMPKα2 in MLO-Y4 cells by transfection with pLKO.1-AMPKα2-shRNA vector and analyzed cell proliferation and the expression of osteogenic markers in MLO-Y4 cells with or without 100 μg/ml leptin treatment through CCK-8, Real-time PCR, Western blot and RNA-seq assay. We found that knockdown of AMPKα2 significantly decreased the mRNA level of AMPKα2 and the cell proliferation of MLO-Y4 cellsas well as the mRNA and protein levels of OPG, OCN, OPN, ALP and BMP6 and the protein expression of p-Smad5/Smad5. However, leptin treatment increased the MLO-Y4 cell proliferation and the expression of these osteogenic markers in MLO-Y4 cells with or without AMPKα2 silencing. Furthermore, RNA-seq assay showed 1019 transcriptors decreased in AMPKα2-silencing group and 995 transcriptors increased in leptin group compared with control group, respectively. 737 transcriptors decreased in AMPKα2-silencing group and 1282 transcriptors increased inleptin group compared with AMPKα2-silencing+leptin group, respectively. These findings suggest that AMPKα2 knockdown inhibited MLO-Y4 cell proliferation and osteogenic marker expressions, which implicates an important role of AMPKα2 in osteogenesis in vitro.